Peningkatan Kemampuan Penalaran Matematis Siswa melalui Model Learning Cycle 7E Berbantuan Aplikasi Symbolab - Fidianti, Serli; Sari, Virgania (Papanda, 2026)
Mathematical reasoning skills are one of the important skills that need to be developed in mathematics learning because they play a role in helping students understand concepts, construct arguments, and draw conclusions logically. However, mathematics learning in schools still tends to focus on procedures and routine exercises, so that students' mathematical reasoning skills have not developed optimally. One alternative learning method that can be applied is the 7E Learning Cycle model assisted by the Symbolab application. This study aims to determine the achievement of learning completeness and the improvement of students' mathematical reasoning skills through the 7E Learning Cycle model assisted by the Symbolab application. This is a quantitative study conducted on 11th grade students at SMK Negeri 3 Semarang. Data were collected using a mathematical reasoning skills test and analyzed quantitatively. The results showed that learning with the 7E Learning Cycle model assisted by the Symbolab application achieved classical learning completeness from the predetermined Actual Completion Limit (BTA) of 42,3. In addition, students' mathematical reasoning skills increased from an average score of 39.76 to 70.67, with an N-gain score of 0.5131, which is in the moderate category. Thus, learning with the 7E Learning Cycle model assisted by the Symbolab application shows an increase in students' mathematical reasoning abilities.